2021
DOI: 10.3390/app11178070
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics in Oral Health and Disease: A Systematic Review

Abstract: Purpose: Probiotics may exclude or antagonize oral pathogens and be useful to prevent oral dysbiosis and treat oral diseases. The objective of this review was to assess the benefits of probiotics in oral health and disease, and in dental practice; Methods: Primary articles published between January 2012 and 30 December 2020 with full text available were searched in PubMed, ClinicalTrials.gov, ScienceDirect, Google Scholar, B-on, and SciELO; Results: The electronic search identified 361 references of which 91 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 111 publications
0
15
0
Order By: Relevance
“…Several studies have shown that probiotic bacterial strains, originating from the indigenous oral microbiota of healthy humans, may have potential application as adjuvants for the prevention and treatment of halitosis [ 113 ]. The aim is to prevent the re-establishment of unwanted bacteria and thus limit the recurrence of oral malodor for an extended period.…”
Section: Treatmentmentioning
confidence: 99%
“…Several studies have shown that probiotic bacterial strains, originating from the indigenous oral microbiota of healthy humans, may have potential application as adjuvants for the prevention and treatment of halitosis [ 113 ]. The aim is to prevent the re-establishment of unwanted bacteria and thus limit the recurrence of oral malodor for an extended period.…”
Section: Treatmentmentioning
confidence: 99%
“…In recent years, a significant number of studies and systematic reviews have been suggesting and showing the benefits of using probiotics as a preventive and therapeutic method for oral infections [ 135 , 136 ]. Several mechanisms of action have been assigned to probiotics to account for their potential as therapeutic treatments for oral diseases, including hampering pathogens colonization by direct competition for nutrients or binding sites, producing antibacterial compounds (e.g., bacteriocins) targeting specific oral pathogens, altering oral biofilm composition and function, modulating signaling and metabolic pathways locally, and improving the immune-inflammatory response [ 135 , 137 ].…”
Section: Current Alternatives To Antibiotics To Prevent and Treat Ora...mentioning
confidence: 99%
“…Probiotics are live organisms that confer health benefits to the host when administered in adequate amounts [8]. Since it is recognized that changes in the composition of dental biofilm play a key role in the initiation and progression of periodontal diseases, the administration of probiotic strains has been proposed to be useful in the prevention and treatment of these diseases [9][10][11][12]. Lactobacillus and Bifidobacterium are the most frequently described probiotics among which Lactobacillus reuteri (L. reuteri) is one of the most studied strains [13].…”
Section: Introductionmentioning
confidence: 99%